Transformations of Lamarckism : From Subtle Fluids to Molecular Biology - Jablonka, Eva; Gissis, Snait, 1945- (Book collections on Project MUSE., 2011)
This title shows the advantages of a Lamarckian perspective on evolution. Indeed the development-oriented approach it presents is becoming central to current evolutionary studies.